Prognostic Significance of Signet-Ring Cell Components in Patients With Gastric Carcinoma of Different Stages - Dong, Xiaoyuan; Sun, Guorui; Qu, Hui; He, Qingsi; Hao, Zhaofan (Frontiers in Surgery, 2021)
Background: Gastric carcinoma (GC) which contains signet-ring cell (SRC) components are frequently observed in postoperative pathological assessment. This study aims to study the prognostic significance of SRC components in GC patients. Methods: From 2003 to 2017, surgically resected primary GC patients were retrospectively reviewed. All enrolled patients were divided into three groups according to the proportion of SRC. The overall survival (OS) and disease-free survival (DFS) of GC patients with different tumor stage were analyzed. Results: Patients with SRC or mixed-SRC were more associated with female, younger age, middle or lower third of the stomach, larger tumor, higher pN stage, and more lymphovascular invasion. For GC patients of stage I, multivariate survival analysis showed that age > 60, SRC components > 50% and pT stage and were independent prognostic factors for OS (all P < 0.05). The 5-year OS of patients with SRC were higher than patients with pure adenocarcinoma (P = 0.021). For GC patients of stage II/ III, multivariate survival analysis showed that age > 60, SRC proportion, surgical types, Borrmann’s type, pT stage, pN stage and lymphovascular invasion were independent prognostic factors for OS (all P < 0.05). The 5-year OS/ DFS of patients with SRC were lower than patients with pure adenocarcinoma (P < 0.001). Conclusions: SRC seemed to be favorable prognostic factor in GC patients of stage I. However, for GC patients of stage II/ III, the SRC components were associated with poor prognosis, independent of other clinicopathological factors.